3-Arylcoumarin inhibits vascular calcification by inhibiting the generation of AGEs and anti-oxidative stress. (31st December 2022) - Li, YuFei; Pan, Yinbo; Wang, Liying; Wang, Xiaojing; Chu, Haiping; Li, Yan; Mu, Yanling; Sun, Jie
Abstract: Objective: This work aims to screen drugs for preventing and treating vascular calcification. Method: We screened a series of 3-arylcoumarins for the detection of vascular calcification-associated factors using human aortic vascular smooth muscle cells. Results: We found that compounds 14 and 32 significantly inhibited alkaline phosphatase (ALP) activity similar to aminoguanidine hydrochloride (AGH) in a cellular model of AGEs-induced calcification. We also found that compounds 14 and 32 could significantly decrease the levels of factors such as AGEs, intracellular calcium ions, and total ROS in the calcified cell model. Further study indicates that compound 14 could significantly inhibit the expression of P-ERK1/2, PKC, NF-κB, RAGE and OPN proteins and increased the expression of SM22-α and PPAR-γ proteins in the calcified cells. Conclusion: We speculate that compound 14 inhibits vascular calcification by inhibiting oxidative stress and inhibiting AGEs production, suggesting that 3-arylcoumarin derivatives are potential candidates for the treatment of vascular calcification. Novelty Statement: Vascular calcification is a process similar to bone formation, which is highly adjustable and active. Currently, there are no specific drugs to delay or reverse vascular calcification. Through the screening of 44 coumarin compounds synthesised by our group, compound 14 was obtained to dose-dependently inhibit the calcification of vascular smooth muscle cells without affecting the normal proliferation of cells, decreasing the intracellular calcium concentration, inhibiting the activity of ALP enzyme. In conclusion, the calcium lowering effect of compound 14 is a potential candidate for drugs for the treatment of vascular calcification.